Метаболические и аутоиммунные корреляты структурных изменений головного мозга больных с рассеянным склерозом = Metabolic and autoimmune correlates of brain’s structural changes in disseminated sclerosis patients - Anatoliy I. Gozhenko (Journal of Education, Health and Sport, 2015)
Gozhenko A I, Naumenko O Y. Метаболические и аутоиммунные корреляты структурных изменений головного мозга больных с рассеянным склерозом = Metabolic and autoimmune correlates of brain’s structural changes in disseminated sclerosis patients. Journal of Education, Health and Sport. 2015;5(1):163-170. ISSN 2391-8306. DOI: 10.5281/zenodo.14792